Implementasi Mode Operasi Cipher Block Chaining (CBC) Untuk Mengoptimalkan Algoritma Affine Cipher Dalam Pengamanan Data - Salman Siregar (Bulletin of Information System Research, 2023)
Confidentiality and security of data is of paramount importance in data communication, both for the purpose of shared security, and for individual privacy. Computer users who want their data not to be known by unauthorized parties always try to find ways to secure the information to be communicated or to be stored. Protection of data confidentiality is increasing, one way is by applying the science of cryptography. Cryptography is one of the sciences used to maintain the confidentiality and security of data that has been developing since ancient Greece. Cryptography is growing from the cruel era to the present. One of the cryptographic methods that is quite reliable, stable and is the parent of the popular cryptographic algorithms today is Cipher Block Chaining (CBC). Cipher Block Chaining (CBC), this mode is a feedback mechanism on a block, and in this case the results of the previous block encryption are fed back into the current block encryption. The trick, the current plaintext block is XORed first with the previously encrypted ciphertext block, then the XOR results are entered into the encryption function. With the Cipher Block Chaining (CBC) algorithm, each ciphertext block depends not only on its plaintext block but also on all previous plaintext blocks.